Participatory Communication in the Gender Equality Awareness Program 'Cerita Bunda' haibunda.com - Iin Yumiyanti*; Ana kuswanti; Munadhil Abdul Muqsith (Riwayat: Educational Journal of History and Humanities, 2024)
Gender inequality in Indonesia is very high and even in 2021, it was the highest in ASEAN. BPS data, in the following years there was a decrease in the gender inequality index, but the decrease was not significant, and it turned out that complaints of cases of violence against women increased. According to Komnas Perempuan, in 2023, the number of complaints of cases of violence against women was 4,374 cases, an increase compared to the previous year. Law Number 40 of 1999 concerning the Press requires the mass media to assist in efforts to increase gender equality. Fulfilling this obligation, Haibunda.com as a mass media created the "Mother Story" program to accommodate women, especially mothers, to voice the gender injustice they experience in their daily lives. This program has successfully invited Haibunda.com readers to participate. The purpose of this study is to analyze how the Schramm model of participatory communication (sender (transmitter), encoder, decoder, interpreter, receiver, message, feedback, medium, and noise) is implemented in the program "Mother Story" Haibunda.com. This research is descriptive qualitative research with data collection through literature studies, observations, and interviews. The results of the study show that the Schramm model of participatory communication is well implemented in the 'Mother Story' program. The type of participation is self-mobilization. The motivation of mothers to send their stories is to voice the injustice they experienced, the participation rate is a partnership. Haibunda.com conducts training and utilizes technology to maintain and increase such participation